2019
DOI: 10.1186/s12913-019-4309-5
|View full text |Cite
|
Sign up to set email alerts
|

Barriers and facilitators to implementing a pragmatic trial to improve advance care planning in the nursing home setting

Abstract: Background The PRagmatic trial Of Video Education in Nursing homes (PROVEN) aims to test the effectiveness of an advance care planning (ACP) video intervention. Relatively little is known about the challenges associated with implementing ACP interventions in the nursing home (NH) setting, especially within a pragmatic trial. To address this research gap, this report sought to identify facilitators of and barriers to implementing PROVEN from the perspective of the Champions charged with introducing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 35 publications
0
18
0
Order By: Relevance
“…Earlier qualitative reports from PROVEN, found ACP champions, in NHs with low intervention fidelity noted that they had limited time to devote to offering and showing the video, particularly in facilities with high staff turnover 37 . Some champions suggested that they would prefer to use the ACP videos on an as‐needed basis to their discretion 38 . Insufficient staff time to implement a new treatment or intervention is not unique to ACP.…”
Section: Discussionmentioning
confidence: 99%
“…Earlier qualitative reports from PROVEN, found ACP champions, in NHs with low intervention fidelity noted that they had limited time to devote to offering and showing the video, particularly in facilities with high staff turnover 37 . Some champions suggested that they would prefer to use the ACP videos on an as‐needed basis to their discretion 38 . Insufficient staff time to implement a new treatment or intervention is not unique to ACP.…”
Section: Discussionmentioning
confidence: 99%
“…The fact that the majority of barriers cut across aspects of both intervention and research implementation demonstrates the high degree to which aspects of the intervention of focus and research protocols can be intertwined within a pragmatic trial . The tension between real-world service delivery and pragmatic trial protocols has been discussed in prior literature [ 12 , 19 , 25 , 26 ]; however, these discussions have largely focused on how attention to external validity can lead to questionable implementation of the intervention and type III error (i.e., the attribution of outcomes to an intervention that was never fully implemented) [ 4 , 19 , 27 , 28 ]. Our findings demonstrate how the real-world research context can impact full implementation of both intervention and research protocols, even when protocols have been developed to accommodate the local service setting (see Table 1 ).…”
Section: Discussionmentioning
confidence: 99%
“…The inner setting where the intervention is delivered is a frequently documented barrier in implementation science and pragmatic trials [ 19 , 32 ], and aspects of the ED’s communication networks, culture, and structure were demonstrated barriers for POINT intervention and research protocols. These issues were apparent at both hospitals, but, while not captured in the interviews, they were much more difficult to address in the urban hospital site where frequent changes in leadership led to less support for the study over time.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations